The historical development of the national service from the era of ancient Egypt to the modern era - Alshamsi, Huda (Journal of Humanities & Social Sciences, 2022)
Nations survive and prosper and maintain their security through armies. Thus, it represents a strong fortress to protect its stability and preserve the security of its people, and thus it secures its state during war and peace. Compulsory service to the people began in prehistoric times and continued until the modern era. In the twenty-seventh century BC, the national service, or what was called the service of science, was known in ancient Egypt until the modern era. This resulted in several results from the researcher’s point of view regarding national service and its importance among people in terms of protection and knowledge of absolute loyalty to the state by presenting it as a national duty. National service was known in the era of ancient Egypt, and it was compulsory through conscription, and it had a strong army. The Assyrians also relied on the national service system, so they conscripted the Assyrians, known for their strength and valour. The Greeks knew the national service system to form an army and they largely adopted the Macedonian and Greek elements. The Romans knew the national service system, and the barbarians were the basis for forming an army to protect the Roman Empire The Mongols relied on skilled workers and professional soldiers from the cities they conquered. During the pre-Islamic period, the Arabs did not know national service or forced conscription, such as the Romans and Persians, but they were interested in preparing armies and were recruiting individuals from all tribes to prepare a strong army. He also knows the search for some of the models in the modern era of the national service.